Home blood pressure measurement for hypertension management in the real world: Do not just measure, but share with your physician - Rhee, Moo-Yong; Munakata, Masanori; Nah, Deuk-Young; Kim, Je Sang; Kim, Hae-Young (Frontiers in Cardiovascular Medicine, 2023)
Introduction Studies of the effectiveness of home blood pressure (BP) measurement on the treatment of hypertension in the real world are sparse, and the results are controversial. There is an efficacy-effectiveness gap in the treatment of hypertension using home BP measurements. We aimed to investigate the effect of reporting home BP to physicians on ambulatory BP control as a factor contributing to the efficacy-effectiveness gap in treating patients with hypertension. Methods We recruited patients ≥20 years of age taking antihypertensive drugs. Office and 24-h ambulatory BP were measured. A questionnaire to the measurement of home BP was conducted. Participants were divided into an HBPM(−) group, home BP was not measured (n = 467); HBPM(+)-R(−) group, home BP was measured but not reported (n = 81); and HBPM(+)-R(+) group, home BP was measured and reported (n = 125). Results The HBPM(+)-R(+) group had significantly lower office systolic BP (SBP, p = 0.035), 24-h SBP (p = 0.009), and daytime SBP (p = 0.016) than the HBPM(−) group, and lower nighttime SBP (p = 0.005) and diastolic BP (DBP, p = 0.008) than the HBPM(+)-R(−) group. In the multivariate analysis, the differences in 24-h SBP, daytime SBP, and nighttime DBP remained significant. There was a significant difference between groups in the target achievement rate of 24-h SBP (p = 0.046), nighttime SBP (p = 0.021), and nighttime DBP (p = 0.023). The nighttime SBP and DBP target achievement rates in the HBPM(+)-R(+) group were higher than those in the HBPM(+)-R(−) group (p = 0.006 and 0.010, respectively). Among patients measuring home BP, the adjusted odds ratio for 24-h and nighttime BP target achievement in the HBPM(+)-R(+) group were 2.233 and 3.658, respectively. Conclusion Home BP measurements should be reported to the treating physician to effectively manage hypertension. Clinical trial registration https://clinicaltrials.gov, identifier NCT03868384.